2010
DOI: 10.1094/fg-2010-0407-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Dry Matter Yield Following Differential Broiler Litter Application from a Soil Enriched with Organic Matter and Phosphorus

Abstract: Broiler litter is often applied to pastures as an organic fertilizer. A history of repeated annual litter application can increase soil‐test P concentrations to levels that can result in degraded water quality if P‐enriched sediment enters waterways after being transported from areas prone to erosion. Nutrient management tools, such as the P Index, are being used in many areas of concentrated broiler production as a means to limit the amount of P added to soil in litter applications. However, it is unclear how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…Annual precipitation amounts were 1033, 1508, and 1239 mm during 2009, 2010, and 2011, respectively, and averaged 1260 ± 138 mm, which was 2.3% above the 30-yr mean annual precipitation for Fayetteville, AR (1232 mm) (NOAA, 2013). Similar to previous studies (Huneycutt et al, 1988;Brye et al, 2010) and as expected, additions of BL increased DM relative to the unamended control (P = 0.05). Averaged over the 3-yr study, annual DM production was 9.9, 12.3, and 18.4 Mg ha -1 for the unamended control, low-BL, and high-BL treatments, respectively, with DM being greater in the high-BL treatment relative to the control and the low-BL treatment being similar to the control and high-BL treatment.…”
Section: Dry Matter Productionsupporting
confidence: 91%
See 2 more Smart Citations
“…Annual precipitation amounts were 1033, 1508, and 1239 mm during 2009, 2010, and 2011, respectively, and averaged 1260 ± 138 mm, which was 2.3% above the 30-yr mean annual precipitation for Fayetteville, AR (1232 mm) (NOAA, 2013). Similar to previous studies (Huneycutt et al, 1988;Brye et al, 2010) and as expected, additions of BL increased DM relative to the unamended control (P = 0.05). Averaged over the 3-yr study, annual DM production was 9.9, 12.3, and 18.4 Mg ha -1 for the unamended control, low-BL, and high-BL treatments, respectively, with DM being greater in the high-BL treatment relative to the control and the low-BL treatment being similar to the control and high-BL treatment.…”
Section: Dry Matter Productionsupporting
confidence: 91%
“…Averaged over the 3‐yr study, annual DM production was 9.9, 12.3, and 18.4 Mg ha −1 for the unamended control, low‐BL, and high‐BL treatments, respectively, with DM being greater in the high‐BL treatment relative to the control and the low‐BL treatment being similar to the control and high‐BL treatment. During the first 6 yr after the initial BL application and before the current study, Brye et al (2010) reported that annual DM production increased over time for the low‐ and high‐BL treatments, whereas annual DM in the unamended control did not change over time. In a concurrent study spanning 8 yr, McMullen (2014) reported no difference in annual DM production from 2008 to 2010, presumably due to shifts in plant species that yielded greater biomass.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Annual aboveground DM production ranged from a low of 4.9 Mg ha −1 in the unamended control in 2003 to a high of 21.6 Mg ha −1 in the high‐BL treatment in 2010 (Table 2). Brye et al (2010) reported that, during the first 6 yr of this study, DM production increased with time for both the low‐ and high‐BL treatments, while DM in the unamended control did not change with time. From 2008 to 2010, annual DM did not differ ( P > 0.05) among BL treatments because plant speciation shifts increased DM variability.…”
Section: Resultsmentioning
confidence: 49%
“…Broiler litter contains numerous plant nutrients, such as N and P, and is often land applied to pastures in the Ozark Highlands to increase yields of tall fescue ( Lolium arundinaceum Shreb.) and other forages (Hileman, 1973; Huneycutt et al, 1988; Brye et al, 2010). In addition to water‐soluble nutrients, BL also often contains trace metals, such as As, Cd, Cu, Se, and Zn (Kunkle et al, 1981; van der Watt et al, 1994; Daigh et al, 2010; D'Angelo et al, 2012), although significant reductions in trace metal concentrations in BL have occurred recently due to stricter regulations on broiler feed additives.…”
mentioning
confidence: 99%